Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Arithmetic Series and Triangular Numbers

  1. Sep 18, 2007 #1
    Re: Arithmetic Series and Factors of Triangular Numbers

    A+C*n, B+F*n, A+E*n, B+D*n are all arithmetic series which I define below
    It is still not clear to me as why
    (A+C*n)*(B+F*n) and (A+E*n)*(B+D*n) are both triangular numbers for all integers n
    Can someone please visit my blog and explain it?
    Perhaps someone can show somehow that
    [tex]8*(A+C*n)*(B+F*n) + 1[/tex] and [tex]8*(A+E*n)*(B+D*n) + 1[/tex] are both perfect squares for all n using Mathematica or some other program.

    --- In Triangular_and_Fibonacci_Numbers@yahoogroups.com, "ramsey2879"
    <ramseykk2@...> wrote:
    > I found a previously unknow property of Triangular Numbers AFAIK.
    > Given that T is a triangular number having exactly M distinct ways
    > pair the product into two factors, A*B with A </= B. For each of
    > M distinct pairs, there are two coprime pairs of integers (C,E) and
    > (E,D)where C*D = the perfect square of integral part of the square
    > of 2*T and E*F = the next higher perfect square and each of the
    > products (A+Cn)*(B+Fn) and (A+En)*(B+Dn) are triangular numbers for
    > integer values of n.
    > As an example.
    > Let T = 666 which can be factored into 6 distinct pairs A,B. The
    > sets (A,B,C,D,E,F) are as follows
    > 1. (1,666,1,1369,2,648)
    > 2. (2,333,1,1369,8,162)
    > 3. (3,222,1,1369,18,72)
    > 4. (6,111,1,1369,72,18)
    > 5. (9,74,1,1369,162,8)
    > 6. (18,37,1,1369,648,2)
    > I don't have a proof of the general result but am working on it.
    Still no proof, however, let ab = T(r) = r(r+1)/2, gcd(n,m) = the
    greatest common divisor of m and n, then the formula for C,D,E and F
    as a function of A and B is

    Case 1, r is even
    C = (gcd(A,r+1))^2, F = 2*(gcd(B,r))^2
    E = 2*(gcd(A,r))^2, D = (gcd(B,r+1))^2

    The determinant
    |C F|
    |E D| = (r+1)^2 - r^2 = 2r+1

    Case 2 r is odd
    C = 2*(gcd(A,r+1))^2, F = (gcd(B,r))^2
    E = (gcd(A,r))^2, D = 2*(gcd(B,r+1))^2

    The determinant
    |C F|
    |E D| = (r+1)^2 - r^2 = 2r+1
  2. jcsd
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Can you offer guidance or do you also need help?
Draft saved Draft deleted